MARLINA SI PEMBUNUH DALAM EMPAT BABAK: MORALITAS DALAM FILM MENURUT ANALISIS SEMIOTIKA - Khirjan Nahdi; Dewi Milandary; Roni Amrulloh (Universitas Hamzanwadi, 2024)
This study aims to determine the meaning of morality in the film Marlina The Killer In Four Acts by Mouly Surya using semiotic analysis. Using descriptive-qualitative research. Data and data sources in this study were obtained from primary data in the form of soft copies of the film Marlina The Killer in four acts, while secondary data were obtained from books, the internet, and journals. Data collection techniques used are documentation and observation techniques. Data analysis using content analysis and semiotic analysis of Charles Sanders Pierce. Validity of data using the power of observers and triagulation. Based on the analysis of the data used, there are 10 categories of morality from 27 data on the film Marlina The Killer in Four Acts: (1) manners in receiving guests as much as 4 data; (2) loyalty to a partner as much as 2 data; (3) courage that Tinggi sebayak 5 data; (4) never give up in all conditions sebayak 1 data; (5) have a polite attitude sebayak 2 data; (6) filial piety to parents sebayak 2 data; (7) the main responsibility as much as 2 data; (8) feel the loss of as much as 1 data; (9) Spread love to each other sebayak 3 data; and (10) Mutual Assistance sebayak 5 data.